Analisis Kreativitas Siswa Dalam Pembelajaran Seni Rupa Membuat Bendera Hias Kelas IV SDN 2 Sadang - Dinar Safitri; Wahyu Amaruddin; Liftiya Ayu Lestari; Dhea Rizqkhita Hijrilliawanni (Jurnal Pendidikan Sosial Dan Konseling, 2023)
Creativity provides significant personal satisfaction and rewards in students' personal development. Therefore, it is important for educators to create an environment that supports the development of students' creativity. One of the class IV learning materials that is considered to be supportive in developing students' creativity is the fine art of making ornamental flags. The aim of this study was to find out the creativity of learners in learning the fine arts of making decorative flags of class IV SDN 2 Sadang. This study uses a qualitative approach that is descriptive in nature. The subjects in the study were grade IV students. Data collection techniques are used in the form of observations, interviews, and documentation. The results of the study showed that through the learning of fine arts making decorative flags, the creativity of fourth grade students of SDN 2 Sadang has a development, whereby students exert all their creations and imagination.